2019
DOI: 10.1016/j.ejca.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

NAPOLI-1 phase 3 study of liposomal irinotecan in metastatic pancreatic cancer: Final overall survival analysis and characteristics of long-term survivors

Abstract: Background: Liposomal irinotecan (nal-IRI) plus 5-fluorouracil and leucovorin (5-FU/LV) is approved for patients with metastatic pancreatic ductal adenocarcinoma (mPDAC) previously treated with gemcitabine-based therapy. This approval was based on significantly improved median overall survival compared with 5-FU/LV alone (6.1 vs 4.2 months; hazard ratio [HR], 0.67) in the global phase 3 NAPOLI-1 trial. Here, we report the final survival analysis and baseline characteristics associated with long-term survivors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
169
8
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 229 publications
(195 citation statements)
references
References 21 publications
13
169
8
5
Order By: Relevance
“…The modified FOLFIRINOX regimen consisted of oxaliplatin 85 mg/m 2 , leucovorin 400 mg/m 2 , irinotecan 150 mg/m 2 , and continuous fluorouracil 2400 mg/m 2 , without bolus fluorouracil. However, mFOLFIRINOX remains a protocol with many side effects, so it could be administered especially to fit patients [22,23], since in the adjuvant setting there are no serological alterations (such as an increase in bilirubin) which may affect the use of irinotecan [24]. Certainly, the choice of adjuvant treatment can also affect the choice of first-line treatment, since the appearance of oxaliplatin neuropathy makes it difficult to subsequently use a combination with nab-paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…The modified FOLFIRINOX regimen consisted of oxaliplatin 85 mg/m 2 , leucovorin 400 mg/m 2 , irinotecan 150 mg/m 2 , and continuous fluorouracil 2400 mg/m 2 , without bolus fluorouracil. However, mFOLFIRINOX remains a protocol with many side effects, so it could be administered especially to fit patients [22,23], since in the adjuvant setting there are no serological alterations (such as an increase in bilirubin) which may affect the use of irinotecan [24]. Certainly, the choice of adjuvant treatment can also affect the choice of first-line treatment, since the appearance of oxaliplatin neuropathy makes it difficult to subsequently use a combination with nab-paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…A subgroup analysis showed that the benefit was maintained in patients that had received 5-FU but not in those previously treated with irinotecan. A recent update of this trial showed an estimated 1-year survival of 26% for nanoliposomal irinotecan plus 5-FU combination versus 16% for 5 FU alone [40].…”
Section: Second-line Systemic Therapy For Metastatic or Local Advancementioning
confidence: 99%
“…In 2015, the FDA approved Onivyde (liposomal irinotecan) for the use in metastatic pancreatic cancer, a disease with a dismal prognosis for affected patients. The phase 3 trial showed an (albeit moderate) extension of overall survival (Wang-Gillam et al, 2016) that was confirmed in a recent follow-up study (Wang-Gillam et al, 2019). In 2017, Vyxeos (liposomal synergistic combination of daunorubicin and cytarabin) was approved for acute myeloid leukemia (Lancet et al, 2018).…”
Section: Introductionmentioning
confidence: 87%